2011
DOI: 10.1007/s11199-011-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

“What I wanted to do was…” Discrepancies Between College Women’s Desired and Reported Responses to Gender Prejudice

Abstract: When experiencing gender prejudice, college women engage in a dynamic decision making process about whether and how to respond. We examined the discrepancy between how college women wanted to respond and how they actually responded to gender prejudice events and explored their reasons for not using a desired response. In this study, 81 college women from the Western United States responded to a qualitative online daily diary about gender prejudice. In 34% (N=265) of the events, the women reported there was a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…For example, in the United States, 2008 presidential campaign in the United States had the potential to have two unknown possibilities: a White female or a Black male for the presidential nomination. Apparently, the less risky unknown was to nominate a Black male as opposed to a White female (Brinkman & Rickard, 2009;Brinkman, Garcia, & Rickard, 2011;Garcia-Retamero & Lόpez-Zafra, 2006;Lehman, 2012;Leppel, 2001;Nadal, Davidoff, Davis, Wong, Marshall, & McKenzie, 2015;Stefurak, Taylor, & Mehta, 2010). ISSN 2329-9150 2016 …”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the United States, 2008 presidential campaign in the United States had the potential to have two unknown possibilities: a White female or a Black male for the presidential nomination. Apparently, the less risky unknown was to nominate a Black male as opposed to a White female (Brinkman & Rickard, 2009;Brinkman, Garcia, & Rickard, 2011;Garcia-Retamero & Lόpez-Zafra, 2006;Lehman, 2012;Leppel, 2001;Nadal, Davidoff, Davis, Wong, Marshall, & McKenzie, 2015;Stefurak, Taylor, & Mehta, 2010). ISSN 2329-9150 2016 …”
Section: Gendermentioning
confidence: 99%
“…Recent research has established that STEM academic programs have traditionally shown discrimination and prejudice toward female students (Berryman-Fink, 2006;Brinkman & Rickard, 2009;Brinkman, Garcia, & Rickard, 2011;Deemer, Smith, Carroll, & Carpenter, 2014;Garcia-Retamero & Lόpez-Zafra, 2006;Lehman, 2012;Leppel, 2001;Levin, Van Laar, & Sidnaius, 2003;Nadal, Davidoff, Davis, Wong, Marshall, & McKenzie, 2015;Rice, Lopez, Richardson, & Stinson, 2013). One such academic discipline, business, traditionally over-represents White males.…”
Section: College Majormentioning
confidence: 99%
“…Similarly, Swim and Hyers () found that only 16% of female participants verbally confronted a confederate who made sexist remarks, even though 75% of the women reported perceiving him as sexist (see also Hyers, ). Research by Brinkman, Garcia, and Rickard (), in which women were asked to keep a record of their experiences with sexism over a 2‐week period, found that women reported significantly more events during which they considered using confrontation than they actually used.…”
Section: Bias‐reduction Strategiesmentioning
confidence: 99%
“…In addition, the decision to confront may depend on personality characteristics including the belief that people can change (Rattan & Dweck, 2010), possessing an optimistic outlook on life and belief that there are more benefits than costs to confronting sexism (Kaiser & Miller, 2004; see also Wellman, Czopp, & Geers, 2009), communal relationship orientation (Gervais et al, 2010), commitment to fighting sexism (Swim & Hyers, 1999), and cultural factors (Lee, Soto, Swim, & Bernstein, 2012). Thus, confrontation can be motivated or inhibited by a variety of factors (see also Brinkman et al, 2011), including the anticipated costs.…”
Section: Discrepancy Strategiesmentioning
confidence: 99%
“…Typically, women perceive hostile sexism negatively, and as a result of being the target of such unfair treatment, experience anger, distress, and physiological arousal and are more likely to engage in collective action on behalf of women (e.g., Becker and Wright 2011;Brinkman, Garcia, and Rickard 2011;Townsend et al 2011). Contrary to these responses, exposure to benevolent sexism instead often leads women to react relatively more positively and engage in stereotypically feminine behaviors unwittingly.…”
Section: Differentiating Between Hostile and Benevolent Sexismmentioning
confidence: 99%